Papuloerythroderma with Associated Non Hodgkin’s Lymphoma : A Rare Entity - Ashish Jagati; Pooja Agarwal; Sabha Neazee; Sanjeev Y Shah (Nepal Journal of Dermatology, Venereology & Leprology)
Papuloerythroderma of Ofuji was first described by Ofuji in 1984. This rare entity is characterized by presence of polygonal, erythematous to brown papules, covering the entire body surface, with a characteristic sparing of body folds (deck chair sign). On hematological investigations, there is characteristic eosinophilia with lymphopenia. It may or may not be associated with underlying malignancies. We report a case of a 81 year male patient where a diagnosis of Papuloerythrodrma secondary to non-Hodgkin`s lymphoma was made based on the criteria laid by Torchia et Al.  Our patient satisfied 4 out of 5 major criteria and all 5 of the minor criteria. This case is reported because of its rarity and characteristic clinical presentation.